Assembly processes underlying bacterial community differentiation among geographically close mangrove forests - Lu Liu; Nan Wang; Min Liu; Zixiao Guo; Suhua Shi (mLife, 2023)
Abstract Bacterial communities play pivotal roles in nutrient cycling in mangrove forests. The assembly of mangrove microbial communities has been found to be influenced by complex factors, such as geographic distance, physicochemical conditions, and plant identity, but the relative importance of these factors and how these factors shape the assembling process remain elusive. We analyzed the bacterial communities sampled from three mangrove species (Aegiceras corniculatum, Bruguiera sexangula, and Kandelia obovata) at three locations along the estuarine Dongzhai Harbor in Hainan, China. We revealed larger differences in rhizosphere bacterial communities among geographical locations than among plant species, indicated by differences in diversity, composition, and interaction networks. We found that dispersal limitation and homogeneous selection have substantial contributions to the assembly of mangrove rhizosphere bacterial communities in all three locations. Following the phylogenetic‐bin‐based null model analysis (iCAMP) framework, we also found dispersal limitation and homogeneous selection showing dominance in some bins. The greater differences among geographic locations may be mainly attributed to the larger proportions of dispersal limitation even at such a short geographic distance. We also found that beta diversity was positively correlated with environmental distances, implying that the more similar environmental conditions (such as rich carbon and nitrogen contents) among plant species may have shaped similar bacterial communities. We concluded that the geographic distances, which are associated with dispersal limitation, played a key role in assembling mangrove rhizosphere bacterial communities, while physicochemical conditions and plant identity contributed less.